Sensibilidade de isolados de fungos entomopatogênicos às radiações solar, ultravioleta e à temperatura - Oliveira, Manuela Teodoro De; Monteiro, Antonio Carlos; Scala Júnior, Newton La; Barbosa, José Carlos; Mochi, Dinalva Alves (Instituto Biológico, 2016)
ABSTRACT: This study aimed to access the sensibility of isolates of the fungus Metarhizium anisopliae (Metsch.) Sorok. and Beauveria bassiana (Bals.) Vuill. to the effect of solar and ultraviolet radiation and temperature. Conidia were exposed for various periods to the rays from a solar simulator at various irradiances, and to light germicidal ultraviolet rays. Conidia of the isolate of M. anisopliae were also exposed to temperatures of 19.5, 24.2 and 31.0ºC and the isolate of B. bassiana to 19.4, 20.8 and 28.3ºC, and also to 18.7, 23.8 and 30.9ºC. The germination of conidia was evaluated by the viability test. The fungal isolates showed to be very sensitive to the solar simulator and ultraviolet rays. Germination of both was significantly decreased starting from 30 minutes of exposure to the rays of the solar simulator. The most severe effect was evidenced by the isolate of B. bassiana with great reduction in conidia germination in all the tested irradiances. Sensitivity to ultraviolet radiation was also great, showing a marked reduction in the germination of M. anisopliae (38.2%) and B. bassiana (65%) conidia after 30 seconds of exposure. The temperature affected the viability of both fungi. Temperatures ranging of 23.8 to 31ºC favor the germination of conidia while temperatures around 20ºC constrained germination.

RESUMO: Este trabalho teve por objetivo avaliar a sensibilidade de isolados dos fungos Metarhizium anisopliae (Metsch.) Sorok. e Beauveria bassiana (Bals). Vuill. ao efeito das radiações solar e ultravioleta e da temperatura. Conídios dos isolados foram expostos, por vários períodos, aos raios de um simulador solar em diversas irradiâncias e a uma lâmpada de raios ultravioleta germicida. Os conídios do isolado de M. anisopliae foram também expostos às temperaturas de 19,5; 24,2 e 31,0ºC, e os do isolado de B. bassiana a 19,4; 20,8 e 28,3ºC, e 18,7; 23,8 e 30,9ºC. Avaliou-se a germinação de conídios pelo teste de viabilidade. Os isolados dos fungos se mostraram bastantes sensíveis aos raios do simulador solar e aos raios ultravioleta. A germinação de ambos sofreu significativa redução a partir de 30 minutos de exposição à radiação do simulador solar. O efeito mais severo foi evidenciado pelo isolado de B. bassiana, com grande redução da germinação dos conídios em todas as irradiâncias testadas. A sensibilidade à radiação ultravioleta também foi grande, pois ocorreu acentuada redução da germinação dos conídios do isolado de M. anisopliae (38,2%) e de B. bassiana (65%) já aos 30 segundos de exposição. A temperatura afetou a viabilidade de ambos os fungos. Temperaturas entre 23,8 e 31ºC favoreceram a germinação dos conídios, enquanto temperaturas próximas de 20ºC dificultaram a germinação.
Sensibility of isolates of entomopathogenic fungi to solar radiation, ultraviolet rays and temperature
Keywords: Beauveria bassiana; Metarhizium anisopliae; biological control; light exposure; Beauveria bassiana; Metarhizium anisopliae; controle biológico; exposição à luz